1977 Biennial Exhibtion. (New York : Whitney Museum of American Art, 1977)
Acconci, Vito ; Africano, Nicholas ; Allen, Terry ; Baldessari, John ; Baltz, Lewis ; Bartlett, Jennifer ; Bochner, Mel ; Brown, Joan ; Burden, Chris ; Celmins, Vija ; Close, Chuck ; Cumming, Robert ; Davis, Stephen A. ; Estes, Richard ; Gorchov, Ron ; Hanson, Duane ; etc.
1977 Biennial Exhibtion, Whitney Museum of American Art, New York, First Floor: February 19 - April 3 1977 ; Third Floor: February 15 - March 27 1977 ; Fourth Floor: February 19 - April 3, 1977
boek